Islamic Social Finance and Maqashid Shariah - Sariah; Nur'aini; Jeni Oktaviani (SMART Insight, 2022)
The purpose of this study is to measure the priority level of Islamic social finance instruments in maqashid sharia. This study used a descriptive qualitative method with an in-depth interview approach. The results show that the implementation of the sharia maqashid theory can give a new color to the discussion of Islamic social financial instruments. There is a meeting point between the objectives of establishing maqashid sharia with the intention of holding Islamic social financial instruments. The two meet in an effort to protect and safeguard human interests in the form of religion, soul, mind, lineage and property.